2017
DOI: 10.1016/j.cnp.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Corticobulbar motor evoked potentials from tongue muscles used as a control in cervical spinal surgery

Abstract: HighlightsThe corticobulbar MEPs from tongue muscles were successfully elicited from 96% of the tested patients.Corticobulbar MEPs from tongue muscles were monitorable from the baseline in 92% of the tested hypoglossal nerves.Corticobulbar MEPs from the tongue muscle might be useful as controls in cervical spine surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…However, there is a paucity of studies that investigated the specific warning criterion for intraoperative MEP of LCN. Only one previous study, including 63 patients who underwent posterior fossa operation, investigated the predictive value of changes in the intraoperative MEPs of CN IX, X, and XII and postoperative functional outcomes of tongue or uvula deviation, implying a final-to-baseline ratio of MEP width could be a possible parameter with a cut-off of 1.03 ms [6]. As this case showed a possi-…”
Section: Case Reportmentioning
confidence: 88%
“…However, there is a paucity of studies that investigated the specific warning criterion for intraoperative MEP of LCN. Only one previous study, including 63 patients who underwent posterior fossa operation, investigated the predictive value of changes in the intraoperative MEPs of CN IX, X, and XII and postoperative functional outcomes of tongue or uvula deviation, implying a final-to-baseline ratio of MEP width could be a possible parameter with a cut-off of 1.03 ms [6]. As this case showed a possi-…”
Section: Case Reportmentioning
confidence: 88%
“…22 These various types of co-worker support could operate as coping resources to help employees manage their tasks more effectively and excel in their job performance. 23 In other words, compared with nurses with less co-worker support, nurses who can get access to more coworker support are likely to draw on more valuable resources to cope with job-related problems and hence perform better in the workplace. As such, the positive effect of ethical leadership on job performance may increase.…”
Section: The Moderating Role Of Co-worker Supportmentioning
confidence: 99%
“…The extant empirical research also showed that co-worker support could moderate the relationship between organizational practices and job performance outcomes, such that the relationship becomes stronger (weaker) when nurses achieve more (less) co-worker support. 23 Thus, we propose that: Hypothesis 4: Co-worker support moderates the relationship between ethical leadership and job performance, such that the relationship would be stronger (weaker) when nurses achieve more (less) coworker support.…”
Section: The Moderating Role Of Co-worker Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Показано, что при электрической стимуляции моторной коры в ходе интраоперационного мониторинга, параметры ВМО с мышц языка составляли: латентность -11,5±1 и 11,5±0,8 мс справа и слева соответственно, амплитуда -1,13±1,04 и 1,15±1,05 мВ соответственно [7]. При ТМС Результаты нашего исследования продемонстрировали, что при определенном положении койла, использовании электродов определенной конфигурации и типа электродов в представленной возрастной группе у всех обследуемых был зарегистрирован воспроизводимый ВМО.…”
Section: ключевые слова: язык нормативные данные транскраниальная магнитная стимуляция вызванный моторный ответunclassified